2000
DOI: 10.1152/physrev.2000.80.4.1267
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans in the Developing Brain: New Conceptual Insights for Old Proteins

Abstract: Proteoglycans are a heterogeneous class of proteins bearing sulfated glycosaminoglycans. Some of the proteoglycans have distinct core protein structures, and others display similarities and thus may be grouped into families such as the syndecans, the glypicans, or the hyalectans (or lecticans). Proteoglycans can be found in almost all tissues being present in the extracellular matrix, on cellular surfaces, or in intracellular granules. In recent years, brain proteoglycans have attracted growing interest due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
446
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(459 citation statements)
references
References 307 publications
(233 reference statements)
2
446
1
4
Order By: Relevance
“…During development of the nervous system, the ECM is suggested to have a role in cell adhesion, cell migration, and axon guidance (Bandtlow and Zimmermann, 2000;Berardi et al, 2004), whereas in the adult brain ECM proteins condensed in perineuronal nets are suggested to maintain established neuronal connections (Murakami and Ohtsuka, 2003). Apart from a role in structural plasticity, perineuronal nets might act in the context of buffers for neurotransmitter release, electrical insulation, and growth factor supply of synapses (Yamaguchi, 2000;Dityatev and Schachner, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…During development of the nervous system, the ECM is suggested to have a role in cell adhesion, cell migration, and axon guidance (Bandtlow and Zimmermann, 2000;Berardi et al, 2004), whereas in the adult brain ECM proteins condensed in perineuronal nets are suggested to maintain established neuronal connections (Murakami and Ohtsuka, 2003). Apart from a role in structural plasticity, perineuronal nets might act in the context of buffers for neurotransmitter release, electrical insulation, and growth factor supply of synapses (Yamaguchi, 2000;Dityatev and Schachner, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that versican V1/V0 and V2 have complementary expression patterns (Bandtlow and Zimmermann, 2000). While versican V1/V0 is mainly expressed in the late stages of embryonic development (Landolt et al, 1995), versican V2 becomes a major chondroitin sulfate proteoglycan in the mature brain (Schmalfeldt et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the hyalectan family, so named for their ability to bind hyaluronan, are versican (also named PG-M), aggrecan, neurocan, and brevican [15]. The characteristic features of hyalectans, also termed lecticans, are their similar globular structures at both N-and C-termini [4,16], and their lectin-like activity [17].…”
Section: Introductionmentioning
confidence: 99%